New diagnostic tools for transport measurements in the scrape-off layer (SOL) of medium-size tokamaks *See reference [1]. (21st March 2019) - Schneider, B S; Ionita, C; Costea, S; Vasilovici, O; Kovačič, J; Gyergyek, T; Končar, B; Draksler, M; Nem, R D; Naulin, V; Rasmussen, J J; Spolaore, M; et al.
Abstract: We present a new diagnostic tool for the determination of various plasma parameters in the edge region of medium-size tokamaks (MST) and stellarators (specifically Wendelstein 7-X) which is under development under the EUROfusion project task force MST2 and S1. This will be a probe head (called the new probe head-NPH) which will carry two cold Langmuir probes, one electron-emissive probe (EEP), two retarding field analysers (RFA) facing upstream and downstream and two magnetic pickup coils. By various adaptors, the same NPH will be used on all three European MSTs (ASDEX Upgrade, TCV and MAST-U) and on Wendelstein 7-X. For the first time the plasma potential in the edge region of MSTs and comparable toroidal fusion experiments will be directly determined by an EEP that will be permanently heated during the measurements. After the introduction and the theoretical background especially of the EEP, the NPH and its components are described in detail. The NPH will be able to measure electron and ion temperature, electron and ion density, cold floating potential, plasma potential and magnetic fluctuations in all three directions of space at two radial positions.